ATTITUDE TOWARDS CONFLICT SITUATIONS IN A TEAM AMONG HANDBALL COACHES - Marta Bon; Mojca Doupona Topič (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The aim of the study was to ascertain the attitude of handball coaches towards conflict situations with regard to selected socio-demographic characteristics. The sample consisted of 58 Slovenian handball coaches working in youth teams. Many differences were discovered between groups of participants. Female coaches held a higher degree of education compared to their male colleagues, and more of them were single (all younger than 31 years). More than half of all participants are involved in an emotional relationship and have children of their own. Generally speaking, coaches have a relatively neutral attitude towards conflicts; they admit their presence, but do not always act as to prevent them from happening. They do not immediately exclude a conflictive player from the team, but try to influence her/him. A conflict with the players or the team management does not divert them from their activity. Female coaches are "more tolerant" of conflicts in their team and seldom intervene between players. Older coaches tend to choose extreme statements. They admit the presence of conflicts, but do not seek reasons for them, often leaving the players to settle the conflict by themselves. Coaches involved in an emotional relationship are slightly more "tolerant" of conflicts. Less experienced coaches perceive conflicts as "less useful" compared to more experienced coaches, while professional coaches agree to a greater extent that conflicts must always be solved. Higher educated coaches tend to notice more conflicts, which probably comes as a consequence of their greater self-criticality. They more frequently see positive sides of conflicts and try to discover the causes for conflict arise.